IMPLEMENTATION OF RSA ASYMMETRIC CRYPTOGRAPHY USING GPG AND KLEOPATRA FOR SCHOOL DATA SECURITY - Ayu Pratiwi; Muhlis Tahir; Nawafilillah; Ach Almas Alvaradis (Jurnal Riset Informatika, 2025)
Digital transformation drives the need for reliable data security systems to protect sensitive information from unauthorized access. This study aims to implement and analyze the use of the RSA cryptographic algorithm based on GPG (GNU Privacy Guard) software and the Kleopatra interface in securing school data. The research method employed is descriptive experimentation with a qualitative approach, conducted at SMK Al-Aziziyah Kwanyar in April 2025. The simulation includes RSA key pair generation, public key exchange, encryption and decryption of school digital data, and digital signature testing. The results indicate that the encryption process using the public key and decryption using the private key are effective and secure. The use of Kleopatra has proven to facilitate key management and cryptographic processes visually. This study emphasizes that the combination of RSA, GPG, and Kleopatra is a practical and efficient solution for data protection in educational environments and can serve as a reference for other institutions in implementing asymmetric cryptography-based digital data security.